2006
DOI: 10.1016/j.cub.2006.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Humans Ignore Motion and Stereo Cues in Favor of a Fictional Stable World

Abstract: As we move through the world, our eyes acquire a sequence of images. The information from this sequence is sufficient to determine the structure of a three-dimensional scene, up to a scale factor determined by the distance that the eyes have moved. Previous evidence shows that the human visual system accounts for the distance the observer has walked and the separation of the eyes when judging the scale, shape, and distance of objects. However, in an immersive virtual-reality environment, observers failed to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 17 publications
5
78
0
Order By: Relevance
“…Hence, the emphasis on precise calibration that we have discussed here and on tests of performance in a variety of tasks under conditions that simulate, in relevant respects, the real world. For example, we have shown in our experiments that walking blind to previously-displayed objects has a similar accuracy to that in a real environment [26]; we have shown that biases in the judgment of distance [25] and object size [6,21] are small, as is the case under real-world conditions.…”
Section: Applicationssupporting
confidence: 56%
See 1 more Smart Citation
“…Hence, the emphasis on precise calibration that we have discussed here and on tests of performance in a variety of tasks under conditions that simulate, in relevant respects, the real world. For example, we have shown in our experiments that walking blind to previously-displayed objects has a similar accuracy to that in a real environment [26]; we have shown that biases in the judgment of distance [25] and object size [6,21] are small, as is the case under real-world conditions.…”
Section: Applicationssupporting
confidence: 56%
“…But two cues that are usually thought of as providing reliable information about the 3D structure of the world, binocular disparity and motion parallax, are still present and should be just as effective at signalling the true size of the room as in a static room. We have investigated this phenomenon in a number of experiments [6,21,24,25]. The important point here is that the isolation and manipulation of binocular disparity and motion parallax cues in this paradigm, independent of other depth cues and while still allowing observers to explore an environment freely, could not be achieved without virtual reality.…”
Section: Applicationsmentioning
confidence: 99%
“…This appears to be a common feature of multimodal integration in decision making (36)(37)(38), magnitude estimation (39)(40)(41), and in combining conflicting visual and interoceptive cues to location (35).…”
Section: Discussionmentioning
confidence: 97%
“…Glennerster, Tcheang, Gilson, Fitzgibbon, and Parker (2006) immersed participants in a large virtual room using a head-mounted display. As participants walked about, the room expanded or contracted by up to a fourfold magnitude.…”
Section: Research Shows That Even If the Environment Does Shrink Or Ementioning
confidence: 99%